Uma análise sobre os estilos de participação entre meninas e meninos nas aulas de educação física - Bergamim, Gabriel Barbosa de Souza (Universidade Federal de São Carlos, 2018)
Scholar Physical education is an environment in wich the students’ participation use to occur in a hierarchical way, different styles of participation can be observed and some power and protagonism relationships are established, especially in team sports. Among the factors that influence those relationships in classes are the student’s motor ability level, their biotype, the amount of class colleagues wherewith their establish relationships and the student’s sex. The scientific literature already points that the last aspect is an important marker. Two researches were used as base to data collection and analysis in current research, one recent and other with more than 30 years (JACO, 2012; GRIFFIN, 1984; GRIFFIN, 1985). Both researches found categories that describe different manners of participating in classes. The current study was characterized as ethnographic, making use of participating observation and the half strutuctured interview; and had as general objective to check wich participation styles can be identified in 6th grade Physical Education classes. The results appoint that there are different participation styles in Physical Education classes, especially the styles: Macho, Lost Soul, Nice Guy, Invisible Player, Protagonist, Figurant, Flutuant and excluded, proposed by Griffin (1984; 1985) and Jaco (2012), likewise the styles Egoist and Distracted, incorporated by the current research; and that the teacher must be alert to any situation that can negative influence on student’s motivation an interest in classes. It was concluded that the teacher should be aware that their students have different manners of understanding and appropriating the classes, being disposed to intervene on constringing situations that can exercise negative influence on students’ motivation, provoking their reflections about how they can act thinking on constructing a space in wich everyone can feel equally included and motivated to participate.
A analysis about the participation styles between girls and boys in physical education classes
Keywords: Educação física escolar; Participação; Gênero; Scholar physical education; Participation; Gender; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::SOCIOLOGIA